A Case of Epididymo-orchitis after intravesical bacille Calmette-Guérin therapy for superficial bladder carcinoma in a patient with latent tuberculosis infection. Issue 1 (December 2016) - Colomba, C.; Di Carlo, P.; Guadagnino, G.; Siracusa, L.; Trizzino, M.; Gioè, C.; Cascio, A.
Abstract Background Intravesical instillation of bacille Calmette-Guérin (BCG) has been established as efficient therapy for superficial bladder carcinoma. Overall, intravesical BCG is well tolerated and results in complications of less than 5 %. However, adverse effects such as granulomatous prostatitis, pneumonitis, hepatitis, sepsis, and hypersensitivity reactions may occur. The reported rate for tuberculous orchitis after BCG intravesical therapy is 0.4 %. Findings We report a case of monolateral tuberculous orchitis occurring one month after the second course of intravescical instillation of bacille Calmette-Guérin in a patient with proven superficial bladder carcinoma and latent tuberculosis infection. Conclusions In our opinion intravesical instillation of BCG should be considered on an individual patient basis, with full patient disclosure of the potentially significant risks. A screening with an intradermal Mantoux before starting the first cycle of BCG instillation should be recommended and isoniazid would be indicated as the treatment for latent tuberculosis infection.